THE IMPACT OF DIGITAL EDUCATION ON MALAYSIAN STUDENTS: A SIGNIFICANT REVIEW - Mohd Fakrul Hafiz Mohd Hanafi; Abdul Hakim Abdullah; Rozaimi Jaafar; Malihah Yumni Mohd Razally (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This scoping article investigates the profound implications of digital education on Malaysian students, aiming to provide a comprehensive overview of its impact. The introduction delineates the evolving landscape of education in the digital age and underscores the increasing reliance on technology for learning. The problem statement identifies key challenges faced by Malaysian students in adapting to digital education, such as technological disparities, access limitations, and potential disparities in the quality of online education. Employing a mixed-methods approach, the methodology combines quantitative surveys to gauge the extent of digital education adoption and qualitative interviews to explore the nuanced experiences and perceptions of students. The expected results anticipate a multifaceted impact, including enhanced accessibility, potential disparities, and varying degrees of adaptability. This study envisions contributing valuable insights to policymakers, educators, and stakeholders in refining digital education strategies tailored to the Malaysian context. In conclusion, the article discusses the broader implications of the findings, emphasizing the need for equitable digital infrastructure and pedagogical innovations to ensure a positive and inclusive educational transformation in Malaysia.